2023
DOI: 10.3390/pharmaceutics15010278
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Particle Size Reduction on the Biorelevant Solubility and Dissolution of Poorly Soluble Drugs with Different Acid-Base Character

Abstract: Particle size reduction is a commonly used process to improve the solubility and the dissolution of drug formulations. The solubility of a drug in the gastrointestinal tract is a crucial parameter, because it can greatly influence the bioavailability. This work provides a comprehensive investigation of the effect of the particle size, pH, biorelevant media and polymers (PVA and PVPK-25) on the solubility and dissolution of drug formulations using three model compounds with different acid-base characteristics (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
3
0
2
Order By: Relevance
“…Wahyudiono et al reported that the injection of a greater concentration of phospholipids, comprising POPC, into a medium brings about an enhancement in liposome size and PDI [ 53 ]. Previous studies by Csicsák et al and Lee mentioned that the reduction in the size of drug particles can increase their surface area, resulting in an improvement in their dissolution and bioavailability, along with a narrow size distribution for drug particles [ 54 , 55 ]. In other words, decreasing the concentration of POPC utilized to produce liposomal CRE-SD may lead to reduced liposome size and PDI, as well as enhanced bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Wahyudiono et al reported that the injection of a greater concentration of phospholipids, comprising POPC, into a medium brings about an enhancement in liposome size and PDI [ 53 ]. Previous studies by Csicsák et al and Lee mentioned that the reduction in the size of drug particles can increase their surface area, resulting in an improvement in their dissolution and bioavailability, along with a narrow size distribution for drug particles [ 54 , 55 ]. In other words, decreasing the concentration of POPC utilized to produce liposomal CRE-SD may lead to reduced liposome size and PDI, as well as enhanced bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Существует несколько подходов, улучшающих абсорбцию вещества в ЖКТ за счет повышения растворимости и/или скорости растворения. Методы повышения растворимости делятся на химические (соли [1], сокристаллы [2] и пролекарства [3]) и физические (комплексообразование [4], создание самоэмульгирующихся композиций, липосомальные технологии [5], микронизация [6], преобразование в аморфную форму и создание твердых дисперсных систем (ТДС) на основе полимерных носителей [7]). Химические модификации имеют весьма ограниченное применение ввиду особенностей активной молекулы.…”
Section: фармацевтическая технологияunclassified
“…Уменьшение размера частиц -одна из самых распространенных технологий повышения растворимости лекарств, поскольку растворимость действующего вещества (ДВ) неразрывно связана с удельной поверхностью частиц. Данный метод широко используется в фармацевтической технологии для повышения биодоступности плохо растворимых активных фармацевтических субстанций (АФС) [6], что позволяет снизить терапевтическую дозу лекарственного вещества (ЛВ) и уменьшить количество побочных эффектов. Однако уменьшение размера частиц оказывает сравнительно небольшое влияние на растворимость ДВ, поскольку повышает не предельную растворимость АФС, а скорость его растворения за счет увеличения площади, доступной для сольватации.…”
Section: фармацевтическая технологияunclassified
“…Over 50 years ago, crystal engineering was applied to a wide range of crystalline powders in order to modulate the performance of Class II and IV raw materials [2][3][4]. Since then, the process of reducing particle size to increase the surface area [5][6][7], as well as obtaining salts [4,8,9], nanocrystals [10,11], cocrystals [12,13], and eutectic mixtures [14][15][16] were some of the approaches that have been explored. Saquinavir base (SQV) (Figure 1) is an anti-HIV drug which belongs to Class II in the BCS.…”
Section: Introductionmentioning
confidence: 99%